Comparative study of DIPSI and WHO 2018 criteria for diagnosis of GDM - Shrestha, Biloni; Pokhrel, L (Nepal Medical College Journal, 2020)
Gestational Diabetes Mellitus (GDM) is an important public health problem. Prevalence has shown an increasing trend and varies based on diagnostic criteria used and the ethnic group studied. It is more common in Asia. Presently, there is no international consensus on the screening and diagnostic criteria for GDM. The Diabetes in Pregnancy Study Group of India (DIPSI) guidelines recommend the non-fasting 75g oral glucose tolerance test (OGTT) as a single-step screening and diagnostic test for GDM, is simple, easy and more feasible. The objective of this study was to compare whether the DIPSI criteria is equally sensitive to WHO 2018 criteria. This was a hospital based cross-sectional study done at Nepal Medical College Teaching Hospital, Kathmandu. Among 425 cases, 25 (5.88%) were diagnosed GDM, 6 (1.41%) were diagnosed only by DIPSI, 5 (1.18) only by WHO 2018 and 14 (3.29%) by both methods. The study showed that the sensitivity of DIPSI was 73.68% and specificity was 98.52%. The agreement between the DIPSI and WHO 2018 criteria ranged from 60% to 80% (Kappa value = 0.68). This study proves that DIPSI criteria is comparable to WHO 2018 criteria and can be adopted in our institution for the diagnosis of GDM as it is more feasible, easy and less expensive.